(untitled) (ЕтноАнтропоЗум, 2015)
Visual records of human behaviour with a camera in Macedonia started at the beginning of the 20th century. Ethnologists’ interest in the camera has been shown by the production of documentaries in the middle of the 20th century and by attempts for outdoor research using camera in the 60s. The use of camera in outdoor research with the current ethnologists is still at a very modest level. In this text I am going to present my personal experience with the camera during site research, mostly in regards to nonmaterial cultural heritage.